MORPHOLOGICAL ANALYSIS OF CEMENTOENAMEL JUNCTION TYPES IN PREMOLARS AND MOLARS OF A SAMPLE OF PAKISTANI POPULATION - Ansari, Asma Saher; Sheikh, Amynah Tariq; Ahmed, Imtiaz; Zaidi, Syed jaffar Abbas (Journal of Ayub Medical College Abbottabad, 2019)
Background: Cementoenamel junction represents the demarcation between enamel covered crown and cementum covered root surface. There is paucity of population specific data of the morphological variability of cementoenamel junctions of permanent and primary teeth. The objective of this study was to investigate the morphological diversity and interrelationship of cementoenamel junction of premolar and molar teeth in permanent dentition of a sample of Pakistani population with potential forensic and anthropological implications. Method: This cross-sectional study was conducted at Oral Biology department of Dr Ishrat ul Ebad khan institute of oral health science, Dow University from March 2016 till September 2016. Seventy-five maxillary and mandibular permanent premolar and molars from adult patients of both sexes were selected and sectioned. Longitudinal ground sections were prepared to study the morphological interrelationship between Cementum and Enamel in each specimen to be viewed under light microscope. A chi-square test was applied between the categorical variables. Results: Results showed 57.3% of sections had cementum overlapping enamel interrelation, 32% showed edge to edge cementum and enamel relation and 9.3% showed that cementum and enamel failed to meet resulting in exposed dentine, while 1.3% sample showed enamel over cementum relation. No significant correlation was found between gender, type of tooth, maxillary, mandibular arches and the morphological variation of CEJ (p>0.05). Conclusion: Based on the findings of this study, it can be concluded that there are considerable morphological variations in CEJ of premolars and molars with preponderance of cementum overlapping enamel in these teeth. Based on these findings, dentists are advised to be mindful of dental procedures involving the CEJ and that these interventions should be performed meticulously avoiding any detachment of cementum and subsequent exposure of dentin resulting in dentin hypersensitivity. Keywords: Cementoenamel junction; light microscopy; ground section